Earnings Announcements And Factors Determining Abnormal Returns: A Study Of Market Efficiency In Indonesia Equity Market - Nainggolan, Rexon (2023)
The main issue in this study is how the market reacts to the information provided during the earnings announcement and relates it to the abnormal returns. The objective is to examine whether the Indonesia equity market (IDX) operates semi-strong form of market efficiency during earnings announcements.